Effect of age and renal function on idarucizumab pharmacokinetics and idarucizumab-mediated reversal of dabigatran anticoagulant activity in a randomized, double-blind, crossover phase Ib study - Glund, Stephan; Kreuzer, Jörg (Clinical pharmacokinetics, 2017)
Background and ObjectivesIdarucizumab is an antibody fragment that specifically reverses dabigatran-mediated anticoagulation. Safety, pharmacokinetics and pharmacodynamics of idarucizumab were investigated in dabigatran-treated, middle-aged, elderly and renally impaired volunteers with characteristics similar to patients receiving anticoagulant therapy.MethodsIn this randomized, double-blind, crossover study, 46 subjects (12 middle-aged, 45-64 years; 16 elderly, 65-80 years; and 18 with mild or moderate renal impairment) received dabigatran etexilate (DE; 220 or 150 mg twice daily) for 4 days. Idarucizumab doses of 1, 2.5 and 5 g or 2 × 2.5 g 1 h apart, or placebo, were administered as a rapid (5 min) infusion ~2 h after DE at steady state.ResultsDabigatran-prolonged diluted thrombin time, ecarin clotting time and activated partial thromboplastin time were reversed to baseline immediately after idarucizumab infusion in all groups. Reversal was sustained with doses ≥2.5 g. Idarucizumab was well tolerated under all conditions. No impact of age on idarucizumab pharmacokinetics was observed; however, subjects with mild or moderate renal impairment demonstrated increased exposure (up to 84 %), decreased clearance and prolonged (by up to 49 %) initial half-life of idarucizumab compared with healthy middle-aged subjects.ConclusionsImpaired renal function was associated with increased exposure and decreased clearance of idarucizumab. Idarucizumab resulted in immediate, complete and sustained reversal of dabigatran anticoagulant activity, and was safe and well tolerated in middle-aged, elderly and renally impaired volunteers. The results support the clinical use of a 5 g dose of idarucizumab.Clinical Trial Registration http://www.clinicaltrials.gov. Unique identifier: NCT01955720.